Conflicts of Interest and Stock Recommendations: The Effects of the Global Settlement and Related Regulations - WANG, Rong (Institutional Knowledge at Singapore Management University, 2006)
Prior research has shown that sell-side analysts in general, and especially those facing conﬂicts of interest driven by investment bank relationships, issue overly optimistic recommendations. This paper studies the eﬀect of regulations on sell-side analysts’ research. These regulations — Rule NASD 2711, Rule NYSE 472, and the “Global Analyst Research Settlement” — attempted to mitigate the interdependence between the research and the investment bank departments of US brokerage houses. The results suggest that the regulations have partially achieved their goal of curbing the conﬂicts of interest’s inﬂuence over analysts’ stock recommendations. After the adoption of the new regulations, the likelihood of receiving an optimistic recommendation no longer depends on whether the ﬁrm had undergone IPO/SEO or whether the brokerage house had participated in any such IPO/SEO as an underwriter. However, analysts are still reluctant to issue pessimistic recommendations for IPO/SEO ﬁrms, and aﬃliated analysts are even more reluctant to be pessimistic about these stocks. We also report an overall change in the distribution of recommendations issued by brokerage houses after the new regulations took eﬀect, in which they leaned towards less optimistic recommendations.